Digital transformation: creating an effective and efficient court in Indonesia - Amarini, Indriati; Saefudin, Yusuf; Kartini, Ika Ariani; Marsitiningsih, Marsitiningsih; Ismail, Noorfajri (Legality : Jurnal Ilmiah Hukum, 2023)
This article discusses digital transformation as an effective and efficient paradigm in court services in Indonesia. The Supreme Court has used digital transformation in court administration by developing an electronic court system or e-Court since 2018. However, procedural law has no legal basis related to electronic trials. The development of online dispute resolution is very fast, while procedural principles regarding due process and neutrality must remain the court's main task. In addition, establishing Internet courts involves three fundamental legal ethical principles: restoring the ceremonial aspects of litigation and creating risk management mechanisms between the legal and technological systems. This study aims to analyze the court's efforts to create an effective and efficient trial in Indonesia. A normative legal method was employed, incorporating various approaches such as the statute, conceptual, and comparative approaches. The research results show that the digital transformation policy was incorporated into the 2010-2035 blueprint of the Supreme Court of the Republic of Indonesia, which has brought about the need to accelerate digital transformation in the justice system. Settlement of civil disputes is carried out using an electronic court (e-court) application with an electronic litigation (e-litigation) mechanism. Meanwhile, the criminal trial was conducted through teleconference media. Still, they have encountered obstacles: limited facilities and infrastructure in conducting the trial, such as internet stability in various regions and limited courtrooms with electronic trial equipment. Need to improve infrastructure and improve the quality of human resources.